Mutant analysis reveals allosteric regulation of ClpB disaggregase - Franke, Kamila B.; Bukau, Bernd; Mogk, Axel (Frontiers in molecular biosciences, 2017)
The members of the hexameric AAA+ disaggregase of E. coli and S. cerevisiae, ClpB and Hsp104, cooperate with the Hsp70 chaperone system in the solubilization of aggregated proteins. Aggregate solubilization relies on a substrate threading activity of ClpB/Hsp104 fueled by ATP hydrolysis in both ATPase rings (AAA-1, AAA-2). ClpB/Hsp104 ATPase activity is controlled by the M-domains, which associate to the AAA-1 ring to downregulate ATP hydrolysis. Keeping M-domains displaced from the AAA-1 ring by association with Hsp70 increases ATPase activity due to enhanced communication between protomers. This communication involves conserved arginine fingers. The control of ClpB/Hsp104 activity is crucial, as hyperactive mutants with permanently dissociated M-domains exhibit cellular toxicity. Here, we analyzed AAA-1 inter-ring communication in relation to the M-domain mediated ATPase regulation, by subjecting a conserved residue of the AAA1 domain subunit interface of ClpB (A328) to mutational analysis. While all A328X mutants have reduced disaggregation activities, their ATPase activities strongly differed. ClpB-A328I/L mutants have reduced ATPase activity and, when combined with the hyperactive ClpB-K476C M-domain mutation, suppress cellular toxicity. This underlines that ClpB ATPase activation by M-domain dissociation relies on increased subunit communication. The ClpB-A328V mutant in contrast has very high ATPase activity and exhibits cellular toxicity on its own, qualifying it as novel hyperactive ClpB mutant. ClpB-A328V hyperactivity is, however, different from that of M-domain mutants as M-domains stay associated with the AAA-1 ring. The high ATPase activity of ClpB-A328V primarily relies on the AAA-2 ring and correlates with distinct conformational changes in the AAA-2 catalytic site. These findings characterize the subunit interface residue A328 as crucial regulatory element to control ATP hydrolysis in both AAA rings.